More Severe Preoperative Kellgren–Lawrence Grades of Knee Osteoarthritis were Partially Associated with Better Postoperative Patient-Reported Outcomes in TKA Patients - Hoorntje, Alexander; Witjes, Suzanne; Koenraadt, Koen L. M.; Aarts, Ruud; Weert, Thomas de; van Geenen, Rutger C. I. (The Journal of Knee Surgery, 2019)
Total knee arthroplasty (TKA) is a successful procedure, although up to 20% of patients remain dissatisfied. Preoperative identification of appropriate TKA candidates is essential for improving satisfaction. This study investigated if preoperative radiographic severity was associated with postoperative pain, function, and quality of life after TKA. We performed a cross-sectional cohort study including 327 TKA patients. Radiographic severity was determined by two independent radiologists using the Kellgren and Lawrence (KL) score. The Knee Injury and Osteoarthritis Outcome Score (KOOS), the New Knee Society Score (New KSS), and Anterior Knee Pain Score (AKPS) were collected. We evaluated the association between KL grade and patient-reported outcome measures (PROMs) with the use of regression analysis techniques. Out of 228 responders, 195 patients completed the questionnaire sufficiently. Forty-seven patients were classified as KL grades 1 to 2, and 144 patients were classified as KL grades 3 to 4. The inter-observer reliability between both radiologists was substantial (ϰ = 0.67). After adjusting for age, sex, and body mass index (BMI), the New KSS subscales symptoms and expectations, and the KOOS subscale quality of life were significantly higher in the KL grades 3 to 4 group. However, neither the remaining KOOS subscales and AKPS nor KOOS change scores differed between both groups. Thus, more severe osteoarthritis (OA) resulted in better outcomes after TKA, although this association was not observed for all PROMs. The use of new PROMs, such as the New KSS, could be more reliable because of lower ceiling effects than the KOOS. Investigating the value of additional methods to assess radiographic severity (such as semi-flexed knee radiographs and MRI) is imperative to reliably identify knee OA.
Keywords: knee arthroplasty; osteoarthritis; radiograph; Kellgren–Lawrence; PROMs